Breaking a monster [videorecording (DVD)] : the story of Unlocking the Truth - Meyer, Luke (RLJ Entertainment, 2016)
Bonding over their love of music, three grade schoolers from Brooklyn, Alec Atkins, Malcolm Brickhouse, and Jarad Dawkins, spend their weekends playing heavy metal/speed punk in Times Square as "Unlocking the Truth." After the band achieves internet fame, the boys are confronted with the realities that come with being rock stars. The documentary chronicles their first year, as the band enters the very adult world of touring, managers, and a $1.8 million record contract.